STRATEGI PEMASARAN MELALUI MEDIA SOSIAL PADA UMKM NyarikKopi MELALUI PENDEKATAN ANALISIS SWOT - Ni Made Ayu Wahyuni; I Wayan Wirga; Ngr Putu Raka Novandra Asta (NETIZEN: JOURNAL OF SOCIETY AND BUSSINESS, 2025)
The purpose of this study is to identify the strengths and weaknesses of internal factors, to examine the opportunities and threats of external factors, and to evaluate the appropriate strategies to be implemented. The data collection methods employed in this research include interviews, observations, questionnaires, and documentation. The analytical techniques used consist of qualitative descriptive analysis, the Internal Factor Analysis Summary (IFAS) matrix, the External Factor Analysis Summary (EFAS) matrix, the Internal-External (IE) matrix, and SWOT analysis. The findings indicate that both internal and external factors influence marketing strategies. Based on the IFAS matrix, the main strength lies in the uniqueness of locally distinctive products, while the primary weakness is the lack of product variation in line with customer preferences. According to the EFAS matrix, the main opportunity is customers’ interest in socially valuable local products, whereas the primary threat is the changing algorithms of social media platforms. The results of the IE matrix place the business in the growth position (cell 5).